The Frequency of Thiopurine Methyl-transferase Polymorphism in Systemic Lupus Erythematosus Patients and Its Association with Azathioprine Induced Adverse Effects (Bangladesh Journal of Medicine, 2026)
Background: Thiopurine S-methyltransferase (TPMT) is the rate-limiting enzyme in the metabolism of azathioprine (AZA). Genetic polymorphisms in TPMT can increase the risk of adverse effects from AZA. AZA is commonly used as an immunosuppressant to maintain remission in patients with Systemic Lupus Erythematosus (SLE). This study aims to investigate the frequency of TPMT polymorphisms in SLE patients . Methods: This post hoc case–control study was conducted at Bangladesh Medical University and the University of Dhaka from July 2022 to January 2023. Adults (18–65 years) fulfilling American College of Rheumatology criteria for SLE were enrolled. TPMT genotyping was performed using polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP). Patients were assigned to AZA (n = 120) or non-AZA (n = 217) groups. Exclusion criteria included recent blood transfusion, use of drugs causing myelosuppression or interfering with AZA/6-MP metabolism, concomitant cyclosporine or mycophenolate mofetil therapy, and pregnancy. AZA was initiated for clinical indications at 1 mg/kg/day, escalated to 2 mg/kg/day after two weeks, and continued with four-weekly assessments for 12 week. Results: The mean age of the AZA group was 28.4 ± 9.5 years; 96.65% were female. TPMT polymorphisms were detected in 12 patients (3.56%), all carrying the TPMT*3C allele. Ten patients developed myelosuppression; among AZA-treated patients with TPMT polymorphisms, six of seven (85.7%) developed myelosuppression. Overall, 16 patients (14.4%) develop AZA-related adverse effects.Conclusion: TPMT polymorphisms were uncommon in this study but strongly associated with AZA-induced myelosuppression. Pre-treatment genotyping may improve the safety of AZA therapy in SLE patients.Bangladesh J Medicine 2026; 37(2): 128-136